2019
DOI: 10.1158/2326-6066.cir-18-0599
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Neoantigen Expression Revealed by Longitudinal Multiomics as a Possible Immune Evasion Mechanism in Glioma

Abstract: Immune-based therapies have shown limited efficacy in glioma thus far. This might be at least in part due to insufficient numbers of neoantigens, thought to be targets of immune attack. In addition, we hypothesized that dynamic genetic and epigenetic tumor evolution in gliomas might also affect the mutation/neoantigen landscape and contribute to treatment resistance through immune evasion. Here, we investigated changes in the neoantigen landscape and immunologic features during glioma progression using exome a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 61 publications
0
42
0
Order By: Relevance
“…Finally, our analyses revealed that immunoediting activity does not vary in glioma over time, though we did observe variation between individual patients. Additional molecular and immunological data are needed to fully understand the impact this variability has on glioma evolution and to devise therapies directed at a glioma's immunogenicity 17 . To this end, we found that clonal neoantigens arising from the IDH1 R132H mutation persisted from the initial tumor into the recurrence, justifying neoantigen vaccine approaches as treatments for initial and recurrent glioma 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our analyses revealed that immunoediting activity does not vary in glioma over time, though we did observe variation between individual patients. Additional molecular and immunological data are needed to fully understand the impact this variability has on glioma evolution and to devise therapies directed at a glioma's immunogenicity 17 . To this end, we found that clonal neoantigens arising from the IDH1 R132H mutation persisted from the initial tumor into the recurrence, justifying neoantigen vaccine approaches as treatments for initial and recurrent glioma 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…The neoantigen expression ratio was reduced in Hot2 and Intermediate tumors but not Hot1 (P = 0.0067), presumably because active immune selection pressures had eliminated tumor cells expressing those neoantigens. 30…”
Section: Tumor Antigensmentioning
confidence: 99%
“…In this case, selection pressure by the immune system forces the tumor entities to reduce its antigenic variety. [29][30][31] This automatically results in lower immunogenic activity on the tumor cell surface. To our understanding these cases are not profiting from PD-L1 blockade.…”
Section: Discussionmentioning
confidence: 99%